Determinants Analysis of Original Local Government Revenue in the Tourism Sector of the Special Regional of Yogyakarta - Sundawan, Hilmy Pradana; Laksmi, Ayu Chairina (Universitas Negeri Yogyakarta, 2024)
ABSTRACTThe aim of this research is to find out the effect of tourism investment, number of tourists, number of tourist attractions, hotel room occupancy rates, and tourism sector local tax on OLGR tourism sector in the Special Region of Yogyakarta. The sampling method used was purposive sampling. The data used is tourism investment, number of tourists, number of tourist attractions, hotel room occupancy rates, tourism sector local tax, and OLGR tourism sector in the Special Region of Yogyakarta in 2004 – 2022. This study is quantitative research with multiple linear regression. The results showed that number of tourist attractions, hotel room occupancy rates, and tourism sector local tax have a significant positive effect on the OLGR tourism sector. Tourism investment and number of tourists have no significant effect on OLGR tourism sector.Keywords: Government accounting, Local taxes, Multiple linear regression, Original local government revenue, Tourism investmentABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh investasi pariwisata, jumlah wisatawan, jumlah objek wisata, tingkat hunian kamar hotel, dan pajak daerah sektor pariwisata terhadap PAD sektor pariwisata di Daerah Istimewa Yogyakarta (DIY). Metode penentuan sampel yang digunakan adalah purposive sampling yaitu data investasi pariwisata, jumlah wisatawan, jumlah objek wisata, tingkat hunian kamar hotel, pajak daerah, dan PAD sektor pariwisata DIY tahun 2004 – 2022. Penelitian ini merupakan penelitian kuantitatif dengan teknik analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa jumlah objek wisata, tingkat hunian kamar hotel berpengaruh positif signifikan terhadap PAD sektor pariwisata. Investasi pariwisata dan jumlah wisatawan tidak berpengaruh signifikan terhadap PAD sektor pariwisata.Kata Kunci: Akuntansi pemerintahan, Investasi pariwisata, Pajak daerah, Pendapatan asli daerah, Regresi linear berganda